Elaboração de uma componente curricular eletiva nas escolas em tempo integral (eemtis) do ceará com foco na olimpíada brasileira de astronomia (oba) - Soares, João Paulo (Universidade Federal Rural do Semi-Árido, 2020)
The present work focuses on the elaboration of a Curricular Component of Astronomy and Astronautics as an Elective Activity to be used in Full Time Schools in the State of Ceará in order to prepare students for the Brazilian Astronomy Olympics. On the theoretical aspects, significant learning and didactic sequence were used for the preparation of the support material used during classes. The objects of knowledge were removed from the invitation to tender organized by the Brazilian Astronomical Society (SAB). The elaboration of the objects of knowledge makes an overview of Astronomy with the following subjects: history of astronomy, solar system, galaxies, life and death of the Stars and ending with Cosmology. In parallel to this study, Astronautics knowledge objects were added: exploration on Mars; space program in Brazil; communication by astronauts in space; space vehicles; orbits of a satellite, the space race; the human body in space and space shuttles. The methodological procedures were based on the assessment of the level of proficiency and the failure rate of students together with the grade obtained by students in the OBA test. The results showed signs of learning in the teaching of Astronomy and Astronautics based on the evaluated indicators. In addition to preparing students for the Olympics, the material offers a range of knowledge focused on Science Education, motivating and encouraging students to scientific research.
Keywords: Ensino de Física; Educação Científica; Astronomia; Physics Teaching; Science education; Ast; CIENCIAS EXATAS E DA TERRA::FISICA